Analisis Hukum Terhadap Penumpang Pesawat Atas Keterlambatan Keberangkatan Penerbangan Domestik di Bandara Internasional Kualanamu Deli Serdang - Sartika Yuli; Taufik Siregar; M Citra Ramadhan (Mahesa Research Center, 2021)
This paper riset aims to examine and analyze the legal rule regarding airlines for passenger aircraft in Indonesia is Law No. 8 of 1999 concerning Consumer Protection, Law no. 1 of 2009 concerning Aviation and Regulation of the Minister of Transportation No. 89 of 2015 concerning Handling Delays in Scheduled Commercial Air Transport Business Entities in Indonesia and Regulation of the Minister of Transportation Number 92 of 2011 amending the Regulation of the Minister of Transportation No. 77 of 2011 concerning the Responsibility of Air Transport Carriers. The factors causing the delay in departure at Kualanamu Deli Serdang International Airport are one of the factors of weather, and technical problems on aircraft but which are more often caused by weather, especially Kuala Lumpur is the hub airport (collecting airport) of several small airports where the weather can change at any time -Time and it is a thing that often happens in Kuala Lumpur. The responsibility of domestic airlines to aircraft passengers who experience delays in departure at Kualanamu Deli Serdang International Airport is to provide compensation and compensation in the form of soft drinks, snacks and heavy meals as well as compensation, depending on the type of delay according to the category, namely: Category 1, 30 to 60 minutes delay, Category 2, 61 to 120 minutes delay, Category 3, 121 to 180 minutes delay, Category 4, 181 to 240 minutes delay, Category 5, more than 240 minutes delay, Category 6, namely flight cancellations, then the airline is obliged to divert to the next flight or refund all ticket costs.